Spider Diversity in Potato Plants Applied with Some Concentrations of Botanical Pesticides Virginia Tobacco Stem Waste - Lalu Ahmad Fauzan; Muhammad Sarjan; Bambang Supeno; Muhammad Hari Aditia Pratama (Master’s Program in Biology, Faculty of Mathematics and Natural Sciences, University of Mataram, 2025)
This study aims to determine the effect of applying various concentrations of botanical pesticides derived from Virginia tobacco stem waste on the diversity of spiders in potato plants. The research was conducted in Sembalun Bumbung Village, Sembalun District, East Lombok Regency, West Nusa Tenggara Province. The method employed was an experimental method with field trials, using a Randomized Block Design (RBD) with six treatments: P0 (control), P1 (abamectin), P2 (Virginia tobacco stem extract 2 ml/L), P3 (Virginia tobacco stem extract 4 ml/L), P4 (Virginia tobacco stem extract 6 ml/L), and P5 (Virginia tobacco stem extract 8 ml/L). The experiment was conducted in three blocks, resulting in 18 experimental units. The results showed that the application of various concentrations of botanical pesticides from Virginia tobacco stem waste did not significantly affect spider diversity in potato plants. However, the P3 treatment (Virginia tobacco stem extract 4 ml/L) exhibited a higher tendency in population, diversity index, abundance index, and dominance index compared to other treatments.